Bore-center annular shaped charges with different liner materials penetrating into steel targets - Xu, Wen-long (2020)
The bore-center annular shaped charge (BCASC) is a new type of shaped charge which can generate alarger-diameter hole in steel targets than classical shaped charges. In this paper, the influence of threeliner materials, i.e. molybdenum, nickel and copper, on BCASC formation and penetrating into steeltargets was investigated by experiment and numerical simulation. The simulation results were wellconsistent with the experimental results. This study showed that, at 0.50Dstandoff distance, the axialvelocity of the molybdenum projectile was lower than that of the nickel and copper projectiles. Thenickel and copper projectiles had almost the same head velocity. The absolute values of the radial ve-locity of the molybdenum projectile head was lower than that of the nickel and copper projectiles.However, at 0.75Dstandoff distance, the absolute values of the radial velocity of the molybdenumprojectile head became much greater than that of the nickel and copper projectile heads. The projectileformed by BCASC with the molybdenum liner had the highest penetration depth of 61.5 mm, which was10.0% and 21.3% higher than that generated by the copper and nickel projectiles.